Afiliator Liability and Digital Evidence in Binary Option Fraud Prosecution: Tanggung Jawab Afiliator dan Bukti Digital dalam Penuntutan Penipuan Opsi Biner - Efendi , Nurul; Multazam, Mochammad Tanzil (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Technological growth has expanded information access but also enabled cybercriminal schemes. Specific background: Binary options trading via the Binomo platform has generated widespread losses and public concern in Indonesia. Knowledge gap: Legal clarity on criminal responsibility for affiliates and admissibility of electronic evidence in Binomo-related cases remains under-discussed. Aims: This study reviews applicable criminal statutes and procedural law to assess potential charges against affiliates and the evidentiary status of digital media. Results: Normative analysis indicates affiliates can be charged under Article 378 juncto Article 55 KUHP, Article 28(1) UU ITE juncto Article 45A(1) UU No.19/2016, and may be implicated in money laundering offenses under Law No.8/2010; electronic evidence is admissible if it meets ITE authenticity criteria and is corroborated by digital forensic expert testimony. Novelty: The paper links affiliate promotional conduct with both fraud and money-laundering frameworks while highlighting procedural challenges for electronic proof. Implications: Findings support stricter enforcement, clearer statutory guidance for prosecuting digital affiliate schemes, and routine use of digital forensics to secure convictions. 3 — Highlight & Keyword (bold header; 3 numbered highlights; 5 keywords single line) Highlights Affiliators’ promotion of Binomo can meet the elements of fraud (Pasal 378 KUHP). Binary-option activity may be prosecuted as money laundering under Law No. 8/2010. Electronic evidence requires digital forensic authentication to be admissible in court. Keywords: Binomo, Affiliator Liability, Electronic Evidence, Fraud, Money Laundering